Container haulage operation and the operational problems of the Konsortium Perkapalan Berhad / Noorizan Ahmad - Ahmad, Noorizan (1987)
The first chapter gave the introduction to this study and an ‘inlook’ into the Konsortium Perkapalan Berhad. The second chapter discussed the procedures, documentation and activities involved in the container haulage operation. It started with order processing until delivery/collection. It ends with the routes covered by the Konsortium, charges on delivery and detention, and fleet maintenance. The third chapter provided the analysis and findings on the performances of the orders, delivery/collection, revenue, operating costs, fleet utilisation and productivity utilisation. Chapter four consists of all the operational problems such as trailer detention, inadequate equipment, frequent breakdowns, clients1 warehousing and repair bay hours, government regulation, errors and delays. The thesis ended with chapter five which comprised of the conclusions and recommendations to the problems. The purposes of the study and the objectives has been achieved. The hypothesis has been tested and proved to be factual. The haulage performance. Analysis showed a bright future for the Konsortium. Recommendations are such as higher detention charges, application of demurrage charges, trailers pooling, extendable trailers, governmental aids, multi-purpose trailers and improved planning.